Electrochemically Enhanced Low-Impedance Ti3C2Tx MXene Epidermal Electrodes for Accurate Electrophysiological Monitoring - Fan, Liubing; Gao, Fangfang; Xu, Liangxu; Xun, Xiaochen; Zhao, Shuchang; Yang, Bing; Bi, Han; Zhao, Xuan; Liao, Qingliang; Zhang, Yue (Nano-Micro Letters, 2026)
Accurate monitoring of electrophysiological signals through epidermal electrodes is crucial for advancing human–machine interfaces and wearable healthcare. While highly conductive materials are conventionally used as epidermal electrodes, their limited electrochemical performance results in high interfacial impedance and consequent signal distortion. Here, we present an electrochemically enhanced low-impedance Ti3C2Tx MXene epidermal electrode for accurate electrophysiological monitoring. The low interfacial impedance is achieved by producing and bridging large Ti3C2Tx MXene nanosheets. Large MXene nanosheets were prepared by combining precursor particle sedimentation with mild shear-assisted exfoliation. An orderly stacking structure was constructed through hydroxyethyl cellulose (HEC) crosslinking large MXene nanosheets to enhance electrochemical performance and flexibility. The epidermal electrodes were fabricated by bonding HEC/MXene film to poly(dimethylsiloxane) substrate via in-situ curing. The MXene epidermal electrodes exhibit lower interfacial impedance (53 kΩ cm2 at 10 Hz) compared to standard Ag/AgCl gel electrodes (436 kΩ cm2 at 10 Hz). This reduction results in a 2.4-fold improvement in signal-to-noise ratio, enabling accurate electrophysiological monitoring. A miniature recording system is integrated with the epidermal electrodes to monitor electrophysiological signals in wearable scenes. Physiological applications have been validated in gesture recognition and health monitoring. Therefore, the electrochemically enhanced low-impedance MXene epidermal electrodes offer a reliable option for acquiring high-fidelity electrophysiological signals. Highlights: 1 Large Ti3C2Tx MXene (~6.5 μm) was prepared through combined precursor particle sedimentation and mild shear-force-assisted delamination to enhance conductivity and capacitance. 2 The epidermal electrode with orderly stacking structure was constructed using hydrogen bonding crosslinking and in-situ curing, demonstrating lower interfacial impedance (53 kΩ cm2 at 10 Hz) and higher signal-to-noise (39 dB) compared to commercial Ag/AgCl gel electrode. 3 The portable recording system was integrated with the epidermal electrodes, enabling applications in muscular status and healthcare monitoring.